Prevention of immune precipitation by purified components of the alternative pathway. - Naama, J K (1985)
The role of the alternative pathway in complement-mediated prevention of immune precipitation has been investigated by the use of BSA-anti-BSA immune complex (IC) purified components. For immune precipitation to be prevented all six alternative pathway components (C3, factors B D, P, H and I) were required. In the absence of one or both of the control proteins H and I, excessive fluid phase turnover of C3 occurred with precipitation of IC. Kinetic studies showed that in the presence of the control proteins, an initial phase of precipitation occurred, and was followed by a phase of resolubilization of IC. When the efficiency of classical and alternative pathways in the prevention of immune precipitation was compared it was found that the classical pathway proteins were more effective than the alternative pathway components. A reaction mixture containing the components of both pathways was no better than the classical pathway protein alone. 125I-C3 was bound to IC which had been rendered soluble in the presence of classical or alternative pathway components. A molar ratio of two molecules C3b:five molecules IgG was calculated. Other complement components which were bound to IC which had been formed in the presence of serum were C1q, C4, C2, C3, C5, P and H. Factors B and I were not detected. Our findings suggest that the alternative pathway is of secondary importance to the classical pathway in the prevention of immune precipitation.